2008
DOI: 10.1074/jbc.m710114200
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Antagonizes Autoinhibition and Activates AMP-activated Protein Kinase in Cells

Abstract: AMP-activated protein kinase (AMPK) serves as an energy sensor and is considered a promising drug target for treatment of type II diabetes and obesity. A previous report has shown that mammalian AMPK ␣1 catalytic subunit including autoinhibitory domain was inactive. To test the hypothesis that small molecules can activate AMPK through antagonizing the autoinhibition in ␣ subunits, we screened a chemical library with inactive human ␣1 394 (␣1, residues 1-394) and found a novel small-molecule activator, PT1, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 58 publications
7
148
2
Order By: Relevance
“…Pang et al (381) have recently reported a second class of small molecule AMPK activator, termed PT1. This compound was identified by a more targeted chemical library screening of 3,600 diverse compounds with the autoinhibited ␣-subunit fragment [␣1 ] and has an EC 50 8 M for ␣1 and 12 M for the corresponding ␣2 (1-398) fragment.…”
Section: F Small Molecule Activatorsmentioning
confidence: 99%
“…Pang et al (381) have recently reported a second class of small molecule AMPK activator, termed PT1. This compound was identified by a more targeted chemical library screening of 3,600 diverse compounds with the autoinhibited ␣-subunit fragment [␣1 ] and has an EC 50 8 M for ␣1 and 12 M for the corresponding ␣2 (1-398) fragment.…”
Section: F Small Molecule Activatorsmentioning
confidence: 99%
“…In the literature, two other direct, small molecule AMPK activators have been reported, PT1 (52) and A-769662 (53), each of which exhibit a distinct mode of activation. Evidence suggests that PT1 antagonizes AMPK autoinhibition by binding to the ␣-subunit near the autoinhibitory domain (AID) (52) and that A-769662 stabilizes the active conformation of AMPK through allosteric binding to the ␥-subunit (53). As the electrostatic potential map of OSU-53 exhibited a high degree of similarity to that of PT1 (Fig.…”
Section: Il-6mentioning
confidence: 99%
“…It seems a more promising selective activator of AMPK (Zhao et al 2007, Scott et al 2008, although it was shown to inhibit the function of the 26S proteasome by an AMPK-independent mechanism (Moreno et al 2008). The second compound is the thiazolidinone PT1 from the Shanghai Institute of Materia Medica (Pang et al 2008). The mechanisms of action of these two compounds are described in these reviews , Fogarty & Hardie 2010).…”
Section: Main Drugs That Are Ampk Activatorsmentioning
confidence: 99%